2021
DOI: 10.3390/medicina57101062
|View full text |Cite
|
Sign up to set email alerts
|

ENT Residents Benefit from a Structured Operation Planning Approach in the Training of Functional Endoscopic Sinus Surgery

Abstract: Background and Objectives: Preoperative planning utilizing computed tomographies (CT) is of utmost importance in functional endoscopic sinus surgery (FESS). Frequently, no uniform documentation and planning structures are available to residents in training. Consequently, overall completeness and quality of operation planning may vary greatly. The objective of the present study was to evaluate the impact of a structured operation planning (SOP) approach on the report quality and user convenience during a 4-day … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Results from the systematic review of literature are summarized in Figure 2. After review of six databases, 86 unique records were identified and 12 were ultimately selected for inclusion in the initial checklist [6][7][8][9][15][16][17][18][19][20][21][22] (Table 1). Of note, none of the selected reports had evidence of content validity for the items included in their respective checklists.…”
Section: Systematic Reviewmentioning
confidence: 99%
“…Results from the systematic review of literature are summarized in Figure 2. After review of six databases, 86 unique records were identified and 12 were ultimately selected for inclusion in the initial checklist [6][7][8][9][15][16][17][18][19][20][21][22] (Table 1). Of note, none of the selected reports had evidence of content validity for the items included in their respective checklists.…”
Section: Systematic Reviewmentioning
confidence: 99%
“…There is a shortage of literature on skull base residency education, but current research suggests widespread model-based training or the use of simulation and cadavers. 1 Due partly to the coronavirus disease 2019 (COVID-19) pandemic, there has been increased interest in the more creative methods of training residents in skull base surgical techniques. The COVID-19 pandemic exacerbated issues for many surgical specialty residents who found their training lacking structure or guidance.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies were able to demonstrate that structured reporting (SR) improves the report quality and time efficiency of HNS by standardizing its content for various educational levels 8 13 14 15 . Furthermore, SR can be considered a valuable tool to improve preoperative evaluation of CT scans in the context of functional endoscopic sinus surgery, both by radiologists and otolaryngologists 16 17 . Due to the standardized structure, SR is associated with a decreased likelihood of missing or misinterpreting key structures, potentially resulting in misdiagnosis.…”
Section: Introductionmentioning
confidence: 99%